Is Poly(Methyl Methacrylate) (PMMA) a suitable substrate for ALD?: A review - Forte, Marta (2021)
Poly (methyl methacrylate) (PMMA) is a thermoplastic synthetic polymer, which displays superior characteristics such as transparency, good tensile strength, and processability. Its performance can be improved by surface engineering via the use of functionalized thin film coatings, resulting in its versatility across a host of applications including, energy harvesting, dielectric layers and water purification. Modification of the PMMA surface can be achieved by atomic layer deposition (ALD), a vapor-phase, chemical deposition technique, which permits atomic-level control. However, PMMA presents a challenge for ALD due to its lack of active surface sites, necessary for gas precursor reaction, nucleation, and subsequent growth. The purpose of this review is to discuss the research related to the employment of PMMA as either a substrate, support, or masking layer over a range of ALD thin film growth techniques, namely, thermal, plasma-enhanced, and area-selective atomic layer deposition. It also highlights applications in the selected fields of flexible electronics, biomaterials, sensing, and photocatalysis, and underscores relevant characterization techniques. Further, it concludes with a prospective view of the role of ALD in PMMA processing.